Azure Cloud Adoption Framework handbook : a comprehensive guide to adopting and governing the cloud for your digital transformation /: a comprehensive guide to adopting and governing the cloud for your digital transformation. (2023) - Kovačević, Saša; Dempsey, Darren
No abstract available